The effects of innovation on Malaysian small medium enterprises' brand performance - Harun, Amran (SAGE Publications, 2017)
The study seeks to examine the effects of innovation towards enhancing brand performance in small edium enterprises (SMEs) inMalaysia. This study is set as a cross sectional and a quantitative study with sample size comprises 304 Malaysian SMEs from the food and beverage (F&B) manufacturing sector based on the list of Fedreation of Malaysian Manufacturers (FMM) directory 2012. A total of 163 completed questionnares were returned showing the response rate of 54%. Smart Partial Least Squared (PLS) version 2.0 software, a structural equation modelling technique was used to analyse data. Results of the study show that innovation positively effects brand performance in the SMEs context. These findings suggest that to hve an efficient brand management in place, films should incorporate innovation in their brand management agencies to further understand the brand managemnet practices among Malaysian SMEs and formulate government support programs towards strengthening the brand-related knowledge and skills among the SMEs.